Role of sustainable development goals in advancing the circular economy: A state-of-the-art review on past, present and future directions - Muhammad Ashraf, Fauzi; Nazim Hanis, Zainal Abidin; Omer, Mazen M.; Kinebe, Ahmed Farouk; Abdul Rahimi, Abdul Rahman (SAGE Publications Ltd, 2023)
The purpose of this study is to review the relationship between the highly anticipated concept of circular economy (CE) and sustainable development goals (SDGs). These two sustainability principles have transformed organizations and countries in their quest to achieve sustainable development. Despite their importance to the business and corporate realm, the discussion of these two concepts has been developed in silos, arbitrarily connected. Through a bibliometric approach, this study reviewed 226 journal publications and 16,008 cited references from the Web of Science (WoS) to understand the past, present and future trends of the two concepts and their impact on the sustainability development. The bibliometric approach of citation, co-citation and co-word analysis uncovers the relevant and significant themes and research streams. Theoretical and practical implications were discussed within the broader business and governance perspective to develop a substantial triple bottom line in creating a sustainable future for civil society.